Physical exercise as an intervention in people at clinical high-risk for psychosis: A narrative review - Marcelo Arancibia; Humberto Pizarro; Rebeca Núñez; Maximiliano Abarca (Medwave, 2023)
The concept of clinical high risk for psychosis has favored research in the neurobiology of the stages prior to psychosis, as well as in preventive interventions. This group is made up of young people with: (1) psychotic symptoms of less intensity or less frequency during a brief time or having genetic history of psychotic disorders associated to a significant deterioration in functioning. The few existing interventions for this population have a low level of evidence. Physical activity and exercise have been shown to be part of the therapy for multiple psychiatric disorders, while a sedentary lifestyle would be a factor that favors psychosis. Indeed, people in clinical high risk for psychosis present a worse physical condition associated with a greater sedentary lifestyle and unhealthy habits. It has been proposed that exercise generates a positive biological effect on the hippocampus and surrounding areas, regions that would be involved in the pathophysiology of psychosis. Some experimental studies have shown a decrease in psychotic symptoms in patients with clinical high risk for psychosis who have followed physical exercise guidelines, as well as morphofunctional changes in brain structures. Although there are barriers to the implementation of this intervention, it is safe and feasible. It is necessary to conduct a greater number of experimental studies on a larger scale to measure its efficacy, generating scientific evidence that will eventually allow physical exercise to be included in clinical practice guidelines as a systematic recommendation for clinical high risk for psychosis.